Enhancing health benefits of milled rice: current status and future perspectives. Issue 29 (17th October 2022) - Kasote, Deepak; Sreenivasulu, Nese; Acuin, Cecilia; Regina, Ahmed
Abstract: Milled rice is an essential part of the regular diet for approximately half of the world's population. Its remarkable commercial value and consumer acceptance are mostly due to its promising cooking qualities, appealing sensory properties, and longer shelf life. However, the significant loss of the nutrient-rich bran layer during milling makes it less nutritious than the whole grain. Thus, enhancing the nutritive value of milled rice is vital in improving the health and wellbeing of rice consumers, particularly for those residing in the low-economic zones where rice is the primary source of calories and nutrition. This article provides a critical review on multiple frontiers of recent interventions, such as (1) infusing the genetic diversity to enrich amylose and resistant starch to reduce glycaemic index, (2) enhancing the minerals and vitamins through complementary fortification and biofortification as short and long-term interventions, and (3) developing transgenic solutions to improve the nutrient levels of milled rice. Additionally, the review highlights the benefits of functional ingredients of milled rice to human health and the potential of enhancing them in rice to address the triple burden of malnutrition. The potential merit of milled rice concerning food safety is also reviewed in this article.